Analisis Matrik SWOT Dalam Pengembangan UMKM Food And Beverage Di Kelurahan Klampis Ngasem - Alexandra Thiara Hidayat; Dinar Erika Febianti; Kayana Violetta (Politeknik Negeri Fakfak, 2024)
The author conducted this research on MSMEs (Small, Micro and Medium Enterprises) in the Klampis Ngasem Village. The purpose of this research is to find out the opportunities, threats, strengths and weaknesses of several active MSMEs, especially in RW 09. The research method used in this study is a quantitative research method, which is carried out based on surveys resulting from interviews with MSME actors. . This study uses data analysis techniques, namely SWOT analysis (Strengths, Weaknesses, Opportunities, Threats). The tools used to compile the determining factors in the sustainability of MSMEs by using the SWOT matrix. With this matrix, it can describe the opportunities and threats as well as the strengths and weaknesses faced by MSME actors. Based on the analysis techniques above, the authors can obtain results with the ST, WT, SO, and WO strategies.